2018
DOI: 10.1002/rcm.8195
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of reaction products of 5‐hydroxytryptamine with methylglyoxal and glyoxal by liquid chromatography/tandem mass spectrometry

Abstract: 5-HT reacts with one or two MGO/GO to form a set of reaction products. The reaction between 5-HT and MGO or GO was faster at higher concentrations of MGO/GO (<10 min), and the same products were found even at physiological concentrations (<48 hrs). The LC-MS/MS (SRM) method can be used to screen the reaction products when present at low level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…The molecular formula of compound 3 was calculated as C 13 H 14 N 2 O 2 based on its positive HRESIMS at m / z 231.11227 (calculated, 231.11280), which is 42.010 26 mass units higher than that of compound 2 , suggesting that compound 3 is a typical β-carboline product produced through the Pictet–Spengler condensation reaction between serotonin and MGO. Therefore, the structure of compound 3 was deduced as shown in Figure , which is consistent with the literature …”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…The molecular formula of compound 3 was calculated as C 13 H 14 N 2 O 2 based on its positive HRESIMS at m / z 231.11227 (calculated, 231.11280), which is 42.010 26 mass units higher than that of compound 2 , suggesting that compound 3 is a typical β-carboline product produced through the Pictet–Spengler condensation reaction between serotonin and MGO. Therefore, the structure of compound 3 was deduced as shown in Figure , which is consistent with the literature …”
Section: Resultssupporting
confidence: 85%
“…MGO is approixmately 10 000–50 000-fold more reactive than glucose and is considered as the most potent glycating agent. , Plasma MGO levels in type 1 and 2 diabetes mellitus groups were around 2 times higher than those in non-diabetic groups. , In addition, many food products and beverages, such as cookies, breads, honeys, coffee, wine, and carbonated soft drinks, represent exogenous sources of MGO. As the reactive dicarbonyl metabolite, MGO can react with not only amino acids in protein but also biogenic amines, such as serotonin. A recent in vitro study reported that MGO could react with serotonin in phosphate-buffered saline (PBS) through the Pictet–Spengler condensation pathway . Three reaction products were tentatively identified through liquid chromatography–tandem mass spectrometry (LC–MS/MS) analysis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations